Ten simple rules for better running. - Lortie, Christopher J; Walshe, Andy; Darling, Hoby; Parker, Jamie (PeerJ Preprints, 2019)
Running is a popular and in many respects intuitive sport. Nonetheless, an extensive body of research literature supports and examines the science of running performance. Here, we used meta-analyses and systematic reviews directly associated with running performance to qualitatively describe ten simple rules for better running. Better running is defined as increases in speed, endurance, or reduced likelihood of injury. The general hypothesis topologically examined was that there is sufficient aggregated evidence to leverage effort and interventions for increased performance in running. This hypothesis was supported with significant big-picture evidence for several pillars of better running including training, recovery, and phenomenological levers specific to this sport. These trends are simplified into ten simple rules for runners and researchers alike.
Keywords: systematic reviews; meta-analysis; synthesis; running research; sport sciences; training; randomized control trials; principles; health